Managing deviant behaviours among undergraduate student users of Federal University Libraries in Southwest, Nigeria (2022)
This study investigated the causes, prevalence and effect of deviant behaviours among undergraduate student users of Federal university libraries in Southwest, Nigeria. Using a descriptive survey research design, 108 librarians from the six Federal university libraries participated in the study. A self-devised structured questionnaire was used for data collection. Data collected were analysed and results presented using table of descriptive statistics, frequencies and percentages. The study revealed that deviant behaviours are opportunistic crimes caused by situational factors including a pervasive view that there is little or no danger of being caught, Porous library security, Poor illumination, lack of vigilance on the part of the employees and feeling that there is little or no punishment when caught. The findings of the study showed that the prevalent deviant behaviours which include stealing, mutilation, defacement of library materials, rudeness to library staff and misuse of library computers, can affect sustainable library growth, destroy library materials, frustrate librarians efforts, affect library image and cost taxpayers money. They reduce library’s service capacity, quality of library resources/ services, increase educational inequality, discourage library usage and reduce users’ perceived value of library services. The study suggests that situational crimes occur when the perceived cost is low and the net benefits associated with the crime is high. Therefore, managing situational crimes in the library implies achieving a balance between situational factors that increase the criminal’s perceived cost and those that decrease the criminal’s perceived benefit. The study recommends the establishment of student disciplinary and counselling units in addition to increasing the cost of crime and the risk of getting caught by increasing library security and imposing stiffer penalties for offenders in order to minimising crime commissioning among undergraduate students in federal university libraries.